Luc Rombouts, Singing Bronze. A History of Carillon Music - Burgers, J.W.J. (BMGN - Low Countries Historical Review, 2017)
Luc Rombouts, Singing Bronze. A History of Carillon Music (Leuven: Lipsius Leuven, 2014, 368 pp., isbn 978 90 5867 956 7).